Medicalization of global health 2: the medicalization of global mental health - Jocalyn Clark (Global Health Action, 2014)
Once an orphan field, ‘global mental health’ now has wide acknowledgement and prominence on the global health agenda. Increased recognition draws needed attention to individual suffering and the population impacts, but medicalizing global mental health produces a narrow view of the problems and solutions. Early framing by advocates of the global mental health problem emphasised biological disease, linked psychiatry with neurology, and reinforced categories of mental health disorders. Universality of biomedical concepts across culture is assumed in the globalisation of mental health but is strongly disputed by transcultural psychiatrists and anthropologists. Global mental health movement priorities take an individualised view, emphasising treatment and scale-up and neglecting social and structural determinants of health. To meet international targets and address the problem's broad social and cultural dimensions, the global mental health movement and advocates must develop more comprehensive strategies and include more diverse perspectives.